Mitigation of firearm recoil - Cross, Alan (Knovel, 2011)
"Calculation of the recoil force should be given special consideration by firearm designers and users because excessive recoil has an adverse effect on accuracy. It is therefore important to obtain an understanding of why excessive recoil occurs and how it might be mitigated."--Description.